IMPLEMENTATION OF LSB AND PLAYFAIR METHODS TO SECURE TEXT FILES INTO WAV AUDIO FILES - Al Akbar, Arief; Sumadi, Muhammad Taufiq; Faldi, Faldi (Jurnal Teknik Informatika (Jutif), 2024)
In the rapidly evolving digital communication era, the demand for information security is escalating. Three main security techniques are required: cryptography, watermarking, and steganography. Despite cryptography and watermarking having detectability weaknesses, steganography emerges as a more reliable choice as it can conceal messages across various media without arousing suspicion. This article discusses the utilization of steganography, particularly the Least Significant Bit (LSB) technique, for embedding messages within audio wave files as the medium. In this research, the author combines steganography with encryption using the Playfair Cipher algorithm to enhance overall data confidentiality. Implementation results demonstrate that the combination of LSB and Playfair methods effectively conceals messages without compromising audio quality. Evaluation of stego quality using PSNR indicates that audio quality remains high after embedding secret messages, with PSNR exceeding 40 dB. Despite successful message extraction during decoding, the message content remains protected and requires decryption to be read. In conclusion, the use of steganography in audio wave files with a combination of Playfair Cipher encryption and LSB methods proves to be an effective approach in preserving privacy and data confidentiality during transmission.